Un santo mulato en la Lima Seiscentista: Martín de Porras - Mariátegui, Javier (2001)
In times of maximun splendor of the peruvian viceroyalty, at the end the 15 th century and beginning of the 16 th, it went throug a stage of marked religiousness and mistycism. Also, there was a proliferation of churches, monasteries and other worship places. Both circumstances lead to a remarkable influence of those aspects realeated with the religious belief on a closed society wich also had a tight relationship between its social layers. It was in this enviroment, in the lower and marginal levels of Lima society, in the surroundings of the city of the Kings, where a mulatto called Martin de Porras lived. He suffered since his childhood and carly adolescence the poverty and limitations tipycal of a black servant community living in a wide black people getto. His annate keenness to service lead him to educate himself as assistant, “barber” herbalist and finally to join, as a “lay brother”, to monastery in Lima. Martin opted for a sort of religious life defined by the compliance to the humblest monastic tasks, as a way of overcoming its own personal condition and giving a meaning of penitence and expiation to his life. In his most frequent place of activity, the infirmary, he took care of those patients coming from the por people with no limit piety and abnegation. He obtained illness relief and healing which was son interpreted as the viceroyal court and even the own viceroy. He was considered as a saint when he died and this was the image that everybody remembered from him since then. He lived during and exceptional part of the Lima history, plenty of mysticism, in wich his life coicided with the lifes of others of other saints as St. Toribio of Mogrovejo, St. Rosa the Lima and the blessed Juan Masias. Some parts of his personality are especially comented, incluiding the symbolism of this “broom”, an instrument of his humble work, wich after him became a symbol of generous devoting to the fellow man.